1987
DOI: 10.1111/j.1467-1770.1987.tb00563.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Religion‐Specific Background Knowledge on the Listening Comprehension of Adult Second‐Language Students

Abstract: This article describes a study assessing the influence of religious‐specific background knowledge on adult ESL listening comprehension. Sixty‐five university‐level students participated in the study. Twenty‐eight students self‐reported being religion‐neutral with virtually no knowledge of Moslem or Christian religious rites. Sixteen of the students declared themselves to be practicing Moslems, and twenty students reported being practicing Christians. The students listened to one passage describing the prayer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 11 publications
6
44
0
Order By: Relevance
“…Significant effects were found for topic familiarity and proficiency with no significant interaction between the two. A facilitative role for BK was also found in Markham and Latham's (1987) study on the effects of religious-specific BK on listening with a clear trend of increase in mean scores when there was a match between passage content (texts of prayer rituals) and religious background. Jensen and Hansen (1995), on the other hand, failed to find reliable BK effects in understanding academic lectures.…”
Section: Listeningmentioning
confidence: 76%
See 1 more Smart Citation
“…Significant effects were found for topic familiarity and proficiency with no significant interaction between the two. A facilitative role for BK was also found in Markham and Latham's (1987) study on the effects of religious-specific BK on listening with a clear trend of increase in mean scores when there was a match between passage content (texts of prayer rituals) and religious background. Jensen and Hansen (1995), on the other hand, failed to find reliable BK effects in understanding academic lectures.…”
Section: Listeningmentioning
confidence: 76%
“…(a) a strong reliance on assumption-based indicators of BK as a predictor of task difficulty and on the basis of group level factors such as academic major (Bei, 2010;Lee & Anderson, 2007), gender (Lumley & O'Sullivan, 2005), choice of topic (Jennings et al, 1999;Tedick, 1990), religion (Markham & Latham, 1987) and cultural background (He & Shi, 2012) rather than measuring BK at the level of the individual. These group-level factors may be weak proxies for BK; for example, the use of academic major, particularly for pre-entry candidates, may simply reflect interest in a field of study.…”
Section: Summary and Methodological Implicationsmentioning
confidence: 99%
“…The results of the study suggested topic familiarity significantly affected listening comprehension at any level of proficiency. These findings corroborate those of an earlier study involving intermediate learners of English (Chiang & Dunkel, 1992) and learners of different nationalities and religious background (Markham & Latham, 1987), as well as a later study on English Academic Preparation (EAP) learners' familiarity with lecture topics (Jensen & Hansen, 1995).…”
Section: Text Authenticity and Relevancesupporting
confidence: 89%
“…That is, the results indicated that cultural familiarization of the text has a significant effect on listening comprehension. Listeners are expected to achieve the writer's intended meaning by combining existing information with what they listen (Bacon, 1992;Chastain, 1988;Chiang & Dunkel, 1992;Long, 1990;Markham & Latham, 1987;Mueller, 1980;Schmidt-Rinehart, 1994). …”
Section: )mentioning
confidence: 99%